How Long Does Antimycobacterial Antibiotic‐loaded Bone Cement Have In Vitro Activity for Musculoskeletal Tuberculosis?. Issue 11 (November 2017) - Lee, Jae Hoo; Han, Chang Dong; Cho, Sang‐Nae; Yang, Ick Hwan; Lee, Woo Suk; Baek, Seung‐Hun; Shin, Jae Won; Husein, Khalid Elfadil Ibrahim; Park, Kwan Kyu
Abstract: Background: Antibiotic‐loaded bone cement is accepted as an effective treatment modality for musculoskeletal tuberculosis. However, comparative information regarding combinations and concentrations of second‐line antimycobacterial drugs, such as streptomycin and amoxicillin and clavulanic acid, are lacking. Questions/Purposes: (1) In antibiotic‐loaded cement, is there effective elution of streptomycin and Augmentin ® (amoxicillin and clavulanic acid) individually and in combination? (2) What is the antibacterial activity duration for streptomycin‐ and amoxicillin and clavulanic acid ‐loaded cement? Methods: Six different types of bone cement discs were created by mixing 40 g bone cement with 1 or 2 g streptomycin only, 0.6 g or 1.2 g Augmentin ® (amoxicillin and clavulanic acid) only, and a combination of 1 g streptomycin plus 0.6 g amoxicillin and clavulanic acid and 2 g streptomycin plus 1.2 g amoxicillin and clavulanic acid. Five bone discs of each type were incubated in phosphate buffered saline for 30 days with renewal of the phosphate buffered saline every day. The quantity of streptomycin and/or amoxicillin and clavulanic acid in eluates were measured by a liquid chromatography‐mass spectrometry system, and the antimycobacterial activity of eluates against Mycobacterium tuberculosis H37Rv, were calculated by comparing the minimal inhibitory concentration of each eluate with that of tested drugs using broth dilution assay on microplate. Results: Streptomycin was detected in eluates for 30 days (in 1 g and 2 g discs), whereas 1.2 g amoxicillin and clavulanate eluted until Day 7 and 0.6 g amoxicillin and clavulanate until Day 3. All eluates in streptomycin‐containing discs (streptomycin only, and in combination with amoxicillin and clavulanic acid) had effective antimycobacterial activity for 30 days, while amoxicillin and clavulanate‐only preparations were only active until Day 14. The antimycobacterial activity of eluates of 2 g streptomycin plus 1.2 g amoxicillin and clavulanate were higher than those of discs containing 1 g streptomycin plus 0.6 g amoxicillin and clavulanate until Day 3, without differences (Day 3, 1 g streptomycin plus 0.6 g amoxicillin and clavulanate: 17.5 ± 6.85 ug/mL; 2 g streptomycin plus 1.2 g amoxicillin and clavulanate: 32.5 ± 16.77 ug/mL; p = 0.109). After Day 7, however, values of the two combinations remained no different than that of Day 30 (Day 30, 1 g streptomycin plus 0.6 g amoxicillin and clavulanate: 0.88 ± 0.34 ug/mL; 2 g streptomycin plus 1.2 g amoxicillin and clavulanate: 0.59 ± 0.94 ug/mL; p = 0.107). Conclusions: Streptomycin, in the form of antibiotic‐loaded bone cement, had effective elution characteristics and antimycobacterial effects during a 30‐day period, whereas amoxicillin and clavulanate only had effective elution and antimycobacterial characteristics during the early period of this study. The two drugs did not interfere with each other during the elution test. Clinical Relevance: This research revealed that combinations of streptomycin and amoxicillin and clavulanate mixed with bone cement are effective for 30 days. Further trials to determine various different combinations of drugs are necessary to improve the effectiveness of treatments for musculoskeletal tuberculosis.